Variation in pre-hospital outcomes after out-of-hospital cardiac arrest in Michigan. (January 2021) - Abir, Mahshid; Fouche, Sydney; Lehrich, Jessica; Goldstick, Jason; Kamdar, Neil; O'Leary, Michael; Nelson, Christopher; Mendel, Peter; Nham, Wilson; Setodji, Claude; Domeier, Robert; Hsu, Anthony; et al.
Abstract: Aim: Care by emergency medical service (EMS) agencies is critical for optimizing prehospital outcomes following out-of-hospital cardiac arrest (OHCA). We explored whether substantial differences exist in prehospital outcomes across EMS agencies in Michigan—specifically focusing on rates of sustained return of spontaneous circulation (ROSC) upon emergency department (ED) arrival. Methods: Using data from Michigan Cardiac Arrest Registry to Enhance Survival (MI-CARES) for years 2014–2017, we calculated rates of sustained ROSC upon ED arrival across EMS agencies in Michigan. We used hierarchical logistic regression models that accounted for patient, arrest-, community-, and response-level characteristics to determine adjusted rates of sustained ROSC among EMS agencies. Results: A total of 103 EMS agencies and 20, 897 OHCA cases were included. Average age of the cohort was 62.5 years (SD = 19.6), 39.7% were female, and 17.9% had an initial shockable rhythm due to ventricular fibrillation or pulseless ventricular tachycardia. The adjusted rate of sustained ROSC upon ED arrival across all EMS agencies was 23.8% with notable variation across EMS agencies (interquartile range [IQR], 20.5–29.2%). The top five EMS agencies had mean adjusted rates of sustained ROSC upon ED arrival of 42.7% (95% CI: 34.6–51.1%) while the bottom five had mean adjusted rates of 9.8% (95% CI: 7.6–12.7%). Conclusions: Substantial variation in sustained ROSC upon ED arrival exists across EMS agencies in Michigan after adjusting for patient-, arrest, community-, and response-level features. Such differences suggest opportunities to identify and improve best practices in EMS agencies to advance OHCA care.